FABRICATION OF p53 PLASMID LOADED PLGA NANOPARTICLES AS A POTENTIAL TREATMENT FOR MALIGNANT MELANOMA - MOHD AFFANDI, NUR KHAIRUNISA; CHE ARIFFIN, SITI ’AISYAH; HARUN ISMAIL, AHMAD FAHMI (International Journal of Allied Health Sciences, 2020)
Malignant melanoma has listed as one of the poor prognosis diseases in the world due to the ineffective treatments. One of the factors of melanoma is the mutated p53 gene which eventually cause cancer formation. Restoring the normal function of p53 has become one of the potential approaches in treating melanoma. In this study, the extracted p53 plasmid was evaluated in terms of pDNA integrity by using agarose gel electrophoresis and encapsulated in double emulsion W/O/W of PLGA nanoparticles. The nanoparticles were characterized in terms of size, charge and morphological surface by using Zeta analysis and scanning electron microscope (SEM). p53 loaded PLGA nanoparticles have been exposed to A375 Human Malignant Melanoma cell lines at different concentration i.e. 0.2, 0.4, 0.6, 0.8 and 1.0 mg/ml for 24 and 48 hours. Cell viability assay (MTT assay) has been performed to evaluate the effectiveness of the cells’ treatment in terms of nanoparticles concentration and duration of nanoparticles exposure. The evaluation of cell viability assay indicated that p53 loaded PLGA nanoparticles significantly reduced the cell viability of A375 as the time of exposure increased. These findings indicated that p53 plasmid loaded PLGA nanoparticles have a potential to become one of the alternative treatments for malignant melanoma.